BAAL/CUP Seminar 2016: New plurilingual pathways for integration: Immigrants and language learning in the 21st century. (14th March 2017) - Bermingham, Nicola; Higham, Gwennan
Abstract : This seminar was held at Heriot-Watt University, Edinburgh, on 27 May 2016. It was jointly organised by BAAL members Nicola Bermingham (Heriot-Watt University) and Gwennan Higham (Swansea University) in collaboration with COST Action IS1306 New Speakers in a Multilingual Europe: Opportunities and Challenges, and supported by the Intercultural Research Centre and the Department of Languages and Intercultural Studies at Heriot-Watt University. Ten papers and two keynote speeches were given. The keynote speakers were Professor Alison Phipps (Glasgow University) and Professor Máiréad Nic Craith (Heriot-Watt University). A round-table discussion was also held, with invited speakers including Ms Mandy Watts from Education Scotland; Professor Bernadette O'Rourke, chair of COST Action IS1306; Dr Cassie Smith Christmas, University of the Highlands and Islands; and Dr Kathryn Jones, Director of Language Policy and Research at the Welsh Centre for Language Planning.